The Effect of Job Stress on Turnover Intention through Job Satisfaction of Government Commercial Bank Employees - ., Sopiah; Mamang Sangadji, Etta (KnE Social Sciences, 2020)
The purpose of this study is to explain the effect of job stress and job satisfaction on staff turnover rates. The study population was drawn from employees of government commercial banks in East Java, Indonesia. With multi-stage sampling techniques, a research sample of 600 people was obtained. The analysis technique uses descriptive analysis and path analysis. The findings of the study prove that job stress has a positive and significant effect directly or indirectly on job satisfaction. keywords: Job stress, job satisfaction, turnover intention